2016
DOI: 10.1128/aac.02652-15
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Mechanisms and Clinical Features of Fluconazole-Nonsusceptible Candida tropicalis Isolates Compared with Fluconazole-Less-Susceptible Isolates

Abstract: eWe investigated the azole resistance mechanisms and clinical features of fluconazole-nonsusceptible (FNS) isolates of Candida tropicalis recovered from Korean surveillance cultures in comparison with fluconazole-less-susceptible (FLS) isolates. Thirtyfive clinical isolates of C. tropicalis, comprising 9 FNS (fluconazole MIC, 4 to 64 g/ml), 12 FLS (MIC, 1 to 2 g/ml), and 14 control (MIC, 0.125 to 0.5 g/ml) isolates, were assessed. CDR1, MDR1, and ERG11 expression was quantified, and the ERG11 and UPC2 genes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 26 publications
5
66
1
Order By: Relevance
“…Moreover, ERG11 expression was even higher among a subset of fluconazole-resistant isolates also resistant to itraconazole and voriconazole. These results were recently echoed by a similar study characterizing 35 C. tropicalis isolates from Korean university hospitals, nine of which were fluconazole-non-susceptible (Choi et al, 2016). While considerable variability in ERG11 expression (~150-fold) was observed in the highly fluconazole-susceptible group, ERG11 expression was significantly higher among both less fluconazole-susceptible (MIC 1–2 μg/ml) and fluconazole-non-susceptible (MIC ≥ 4 μg/ml) isolates.…”
Section: Azole Antifungal Resistance Mechanismsmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, ERG11 expression was even higher among a subset of fluconazole-resistant isolates also resistant to itraconazole and voriconazole. These results were recently echoed by a similar study characterizing 35 C. tropicalis isolates from Korean university hospitals, nine of which were fluconazole-non-susceptible (Choi et al, 2016). While considerable variability in ERG11 expression (~150-fold) was observed in the highly fluconazole-susceptible group, ERG11 expression was significantly higher among both less fluconazole-susceptible (MIC 1–2 μg/ml) and fluconazole-non-susceptible (MIC ≥ 4 μg/ml) isolates.…”
Section: Azole Antifungal Resistance Mechanismsmentioning
confidence: 79%
“…Molecular characterization of azole-resistant clinical C. tropicalis isolates has also revealed alterations in the ergosterol biosynthetic pathway (Vandeputte et al, 2005; Eddouzi et al, 2013; Jiang et al, 2013; Choi et al, 2016). A fluconazole-resistant C. tropicalis isolate recovered from a clinical blood specimen from Tunisia was found to have mutations in both ERG3 and ERG11 which were individually observed to be detrimental to ergosterol biosynthesis when heterologously expressed in S. cerevisiae (Eddouzi et al, 2013).…”
Section: Azole Antifungal Resistance Mechanismsmentioning
confidence: 99%
“…Methodological issues, including pH value and incubation time, were shown to impact the degree of resistance (15)(16)(17), and some authors report more trailing with the EUCAST method than with CLSI at 24 h (22% versus 1.7%) (18). In Candida albicans, variable regulation of drug resistance genes was observed for isolates trailing by the 48-h CLSI method (19), and various drug resistance mechanisms have been implicated in azole resistance in C. tropicalis (20)(21)(22). Yet, it is unknown if trailing is related to the variable regulation of epigenetic traits or resistance mechanisms.…”
mentioning
confidence: 99%
“…Significant up-regulation of SKN1 expression and to a lesser extent KRE1 was observed in Candida biofilms treated with amphotericin B alone or in combination. Choi et al 38 revealed up-regulation of CDR1, MDR1, and ERG11 genes in fluconazole-nonsusceptible C. tropicalis isolates. Fernandes et al 39 showed that C. tropicalis resistance to voriconazole is unable to control biofilms, and the up-regulation of ERG genes is likely to be probable molecular mechanism of Candida biofilm resistance.…”
Section: Resultsmentioning
confidence: 99%